Expectations for tourist development: examining the roles of capacity building and empowerment - Matthews, Drew (My University, 2012)
Rural communities often view small-scale, community-based tourism development as a viable opportunity for economic and community development (Timothy, 2002; Beeton, 2006; Reid, 2003). Unfortunately, the process of developing a successful tourism product can be beyond the capabilities of these communities (Joppe, 1996). Capacity building and empowerment are seen as two useful strategies for enabling people to partake in a variety of development initiatives, including tourism development (Moscardo, 2008; Sofield, 2003). Capacity building is a concept that has been used extensively in international development and is the primary focus of the United Nations Development Programme‟s efforts to alleviate global poverty (Fukuda-Parr, Lopes and Malik, 2002; Eade, 1997). Empowerment has also been used heavily within an international context, although it tends to focus specifically on disadvantaged sub-groups within a larger population, most commonly indigenous peoples and women (Sofield, 2003; Malhotra & Schuler, 2005). Both of these concepts have also been examined and used in the field of tourism development (Moscardo, 2008; Scheyvens, 2002). However, there has been little research that examines the relationship between the two concepts, and none from the perspective of the community members engaged in the tourism development process.
Keywords: Tourism development; Capacity building